Hausa vowels and pronunciation of words by Yoruba native speakers learning Hausa - Maikanti, Sale; Burkhardt, Jurgen Martin; Thai, Yap Ngee; Husain, Salina; Oludare, Oluwadoro Jacob (Universidad del Zulia * Facultad Experimental de Ciencias, 2019)
This study examines the production of 10 monophthongs, and 2 diphthongs of Hausa with the aim of identifying how Yoruba speakers commit errors in the pronunciation of disyllabic Hausa words in the first and second syllables respectively by using a quantitative method with 9 participants (males and females). The results of both the shared and unshared vowels appear to be non-significant for being greater than p˃.005 in the first and second syllables even though their level of performance indicates there are differences. In conclusion, the government should ensure the availability of instructional materials in schools.